An Optimization Strategy for Scheduling Various Thermal Energy Storage Technologies in Office Buildings Connected to Smart Grid. (November 2015) - Finck, Christian; Li, Rongling; Zeiler, Wim
Abstract: An optimization strategy for scheduling various thermal energy storage capacities in an office building is investigated. An activated building wall (building thermal mass), a phase change material (PCM) tank, a hot water (HW) tank and a thermochemical material (TCM) storage are simulated and their charging and discharging behavior are optimized. Therefore, a case study is performed using a very simplified room model (office) and typical weather data for the Netherlands. To model the storage's scheduling behavior for control and optimization, a resistance capacitance (RC) network is applied. The RC network represents the critical energy storage parameters for optimization and control. The minimization of electricity costs is defined as optimization objective towards the Smart Grid. Cost saving potentials up to 12.5% are calculated using an electrical heat pump and a solar collector for heating the room and charging the thermal energy storage capacities.